Influence of Model Assumptions on Radial Flow Investigations in Heavy-Ion Collisions - Kozik, T.; Majka, Z.; Planeta, R.; Staszel, P.; Wolanin-Statek, A.; Smoluchowski, M.; Kowalski, S.; Zipper, W.; Cibor, J.; Kozik, E.; Nicolis, N. G. (HNPS Advances in Nuclear Physics, 2021)
An effective way for the investigation of nuclear matter under the extreme conditions of high density and temperature is the study of nuclear fragmentation, realized in intermediate-energy heavy-ion collisions. The potential energy accumulated in the compression zone of the collision is converted into collective flow of matter in the later stages of the reaction. During the expansion of the system, fragments are formed in a clusterization process. In the final stage of the reaction, the fragments are moving along Coulomb trajectories and may deexcite by particle emission or secondary break-up. In order to verify the influence of the collective energy on the experimental energy spectra and extract quantitative information on the thermal and collective components, a model simulation was developed. In this procedure, the evolution of the disintegrating system in a multifragmentation process was described after the freeze-out stage with a Monte-Carlo approach. A reconstruction procedure for the fragment kinetic energies has shown the possibility to obtain the thermal and collective components from measured fragment spectra. In the present work, we scrutinize the model simulation for the evolution of the disintegrating system by testing the sensitivity of the collective expansion energy extraction on the model assumptions concerning the freeze-out characteristics, such as the size and shape of the freeze-out volume. Furthermore, thermal aspects of the early stage of the expansion are tested with an examination of the relationship between the assumption of the degree of thermalization of the emitting source and the extracted value of the collective energy.